Molecular characterization of colorectal cancer (CRC) using next generation sequencing (NGS) in bridging the gap between research and clinical practice: from biomarker discovery to clinical implementation - Hafeez Abiola Afolabi; Salzihan Md Salleh; Zaidi Zakaria; Ch’ng Ewe Seng; Siti Norasikin Mohd Nafi; Ahmad Aizat Bin Abdul Aziz; Wan Mohd Nazri Wan Zainon; Ahmad Adebayo Irekola; Yusuf Wada; Sameer Badri Al-Mhanna; Rashidat Folashade Elesho (Discover Oncology)
Abstract Background Colorectal cancer (CRC) is the second most common cancer in men and third in females, a heterogeneous disease involving multistep mechanisms that represents 10% of all cancers globally. This study investigates gene mutation profiling in CRC using Next-Generation sequencing machine. Method Formalin-fixed paraffin-embedded tissues of 30 CRC patients were retrieved and reviewed. DNA was isolated from selected tissues. Desirable quality check using Qubit and Nanoquant machine was done, and desirable libraries prepared were loaded into the sequencer for sequencing. Using Illumina BaseSpace and Illumina Variant interpreter, generated FastQ data were treated for annotation, alignment, and mapping with reference genome. Sequencing-runs with Phred-score ≥ 30 were selected as desirable runs. Finally, the variants were validated on NCBI-dsSNP and Ensembl databases for clinical consequence interpretations. Results Overall, patient distribution consists of 12(40%) females and 18 (60%) males with mean age (53.2 + 5.3). most patients were in TNM stage-3: 53.3% (15/30) and the least was Stage-4: 20%(6/30) respectively. Overall, 73.3%: (22/30) completed the sequencing, and 552 mutations involving 29 genes and 12 chromosomes were detected. The most upregulated variants are KIT:68(12.3%), FGFR4:61(11.1%), EGFR:60(10.9%), ALK:53(9.6%), DCUN1D1:41(7.4%), PDGFR:40(7.2%), KRAS:33(6.0%), CDK4:27(4.9%), FGFR3:26(4.7%), MTOR:14(2.6), while NRAS , CDK6, PIK3CA, and RET each has 13(2.4%) apiece. Chromosomes 4:134/55(24.2%), chr7:84/552(15.2%), chr12:71/552(12.9%), chr5:64/552(11.6%), chr2:61/552(11.1%), chr3:54/552(9.8%), and chr1:43/552(7.8%) are the most involved chromosomes. Nine genes (APC, NRAS, ALK, PIK3CA, KRAS, IDH1, FGFR1, ERBB2, and ESR1) are identified as pathogenic-causing variants in CRC. Conclusion This is the first NGS-based molecular study on FFPE-CRC tissues in hospital-USM that showed the most upregulated variants in CRC and identified nine genes as crucial pathogenic variants.